A compressive survey on different image processing techniques to identify the brain tumor - Bhagavan, K; S. Sagar Imambi, Dr; Shahana Bano, Dr (International Journal of Engineering and Technology, 2018)
Medical imaging technology has revolutionized health care over the past three decades allowing doctors to detect, cure and improve patient outcomes. Medicinal imaging makes picture of the internal organs, parts, tissues and bones for therapeutic examination and research pur-poses. It can likewise be utilized to think about elements of a few organs. X-ray and CT scanner are the two greatest after-effect of headway of imaging methods supplanting 2D procedures. X-ray is the standout amongst the most critical pre-processing ventures in tumor discovery. Magnetic resonance imaging (MRI) is really an imaging procedure in the restorative field. It is utilized as a part of radiology for imagining interior structures of the body and furthermore how they work. X-ray gives you the 3D picture of the inside bits of the body which enables the specialist to dissect the infection or tumor effortlessly though old imaging procedures like x-beam imaging gives you 2D pictures. In this paper we are introducing distinctive systems for distinguishing, preparing restorative pictures. Â